Pembinaan Administrasi Keuangan Dan Pemasaran Digital Pada UMKM Karunia Desa Sawahan Mojokerto - Hidayat, M. Syamsul; Dwihandoko, Toto Heru; Setyariningsih, Eny (Fakultas Ekonomi Universitas Islam Majapahit, 2022)
Most of the MSME entrepreneurs in trade management are still traditional, so that the results of their business are only sufficient for daily life and some other needs. Bookkeeping has not been recorded in an orderly manner, let alone simple financial reports do not even exist. Likewise, the marketing system carried out by MSME Karunia Desa Sawahan, Mojosari District is also still far from modern. Where marketing is still being carried out by relying on traditional marketing by relying on salespeople. This causes the amount of costs and benefits to be unknown and a good marketing system to be known. Besides that, in the current economic conditions in Indonesia, The era of the industrial revolution society 4.0 and the COVID-19 pandemic period requires modern marketing with a digital system. Therefore, it is necessary to develop knowledge and skills so that their businesses (MSMEs) can be more advanced and develop by incorporating digitalization and digital marketing strategies (digital marketing). help use websites, blogs or social media as promotional media and sales strategies (Umar et al., 2020) In order to overcome these problems, the Service Team of the Faculty of Economics, Majapahit Islamic University, designed a solution by providing assistance in Financial Administration and Digital Marketing so that partners understand how to have a good financial system and good marketing management by utilizing digital technology (Digital Marketing). As said by Wang (2010),